HUBUNGAN KEPEMIMPINAN DENGAN SEMANGAT KERJA KARYAWAN PADA JASA PERHOTELAN (Kasus Hotel Benteng Pekanbaru) - Asmadewira "; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This reseacrh was conducted at hotel of fortress pekanbaru. The study aims to determine the relationship of ledership whit employee morale hotel pekanbaru fort. Leadeship as a variabel (X) the study took the number of respondent as many 45 people.Of data obtained from quetinnaires and forther if to thn tested using the help of ststistical analysis such as correlation product moment pearson and t test by using ald of application SPSS.The result of studes using correlation product moment pearson suggesting that relationship of ledership and employee performance is quite good with a correlation value (r) of 0,620. While the result of testers t test showed t count is grreater than t table (5.177 > 2.106) this suggest that the leadership has a relationship with morale at the castle.Keywords: Leadership, Morale